Asymptotics of Blaschke Products the Counting Function of Zeros of Which Is Slowly Increasing - Zabolotskii, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We find the asymptotics as z→ 1 for the Blaschke product with positive zeros the counting function of which n(t) is slowly increasing, i.e., n((t+ 1)/2) ∼ n(t) as t→ 1.